Effects of CDX2 on prognosis and chemotherapy responsiveness in mismatch repair‐deficient colorectal cancer. Issue 6 (24th July 2018) - Ryan, É. J.; Creavin, B.; Khaw, Y. L.; Kelly, M. E.; Mohan, H. M.; Geraghty, R.; Ryan, E. J.; Kennelly, R.; Hanly, A.; Martin, S. T.; Fennelly, D.; McDermott, R.; et al.
Abstract : Background: Caudal‐related homeobox transcription factor 2 (CDX2) is an intestine‐specific transcription factor implicated in tumour differentiation, proliferation, cell adhesion and migration. Negative CDX2 status (CDX2−) is associated with worse prognosis in colorectal cancer and may identify high‐risk stage II disease that benefits from adjuvant chemotherapy. This observational study investigated whether CDX2− is associated with prognosis or response to chemotherapy in the mismatch repair‐deficient (dMMR) phenotype of colorectal cancer. Methods: Patients with resectable dMMR colorectal cancer were eligible for inclusion. The prognostic and predictive value of CDX2 expression on the presence of lymph node metastasis (LNM) and survival was investigated. CDX2 status was determined via immunohistochemistry using the Leica Bond™ CDX2 (clone EP25) ready‐to‐use primary antibody. Results: Some 235 of 238 consecutive dMMR tumours were assessed for CDX2 status. CDX2− was observed in 15·7 per cent of colorectal cancer. Interobserver agreement was excellent ( κ = 0·863; P < 0·001). CDX2− was significantly associated with female sex, increased size, advanced stage, worse conventional and poorly differentiated cluster (PDC) grade, mucinous morphology, perineural and lymphovascular invasion, and pN status (all P ≤ 0·038). CDX2− was not associated with LNM or survival in multivariable analysis. Independent predictors of LNM were PDC grade (odds ratio (OR) 4·12, 95 per cent c.i. 1·76 to 9·63; P = 0·001) and extramural venous invasion (OR 3·79, 1·62 to 8·85; P = 0·002). Budding (hazard ratio (HR) 2·79, 95 per cent c.i. 1·60 to 4·87; P < 0·001), pT status (HR 3·59, 1·29 to 10·01; P = 0·015) and adjuvant chemotherapy (HR 2·07, 1·15 to 3·74; P = 0·016) were independently associated with worse disease‐free survival. Conclusion: CDX2− does not confer a worse prognosis in the dMMR phenotype of colorectal cancer. The MMR status of patients with colorectal cancer should be determined before assessing CDX2 status. Abstract : A lack of caudal‐related homeobox transcription factor 2 (CDX2) expression does not confer a worse prognosis in the mismatch repair‐deficient (dMMR) subtype of colorectal cancer (CRC). The MMR status of CRC should be determined prior to any assessment of CDX2 status. Use of adjuvant chemotherapy is associated with worse disease‐free survival in dMMR compared to surgery alone. Investigation of novel therapeutic strategies to provide alternative approaches for high‐risk dMMR CRC is required. CDX2 is no prognostic factor in mismatch repair deficient colorectal cancer